2020
DOI: 10.1371/journal.pone.0243697
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and human-nature relationships: Vermonters’ activities in nature and associated nonmaterial values during the pandemic

Abstract: The COVID-19 pandemic has rapidly modified Earth’s social-ecological systems in many ways; here we study its impacts on human-nature interactions. We conducted an online survey focused on peoples’ relationships with the non-human world during the pandemic and received valid responses from 3,204 adult residents of the state of Vermont (U.S.A.). We analyzed reported changes in outdoor activities and the values associated with human-nature relationships across geographic areas and demographic characteristics. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 73 publications
7
103
1
Order By: Relevance
“…These findings were similar to those found in a majority white, high-income sample from Vermont during the pandemic, showing that participation in nature-related physical activity increased and was associated with income, sex, and employment [45]. Likewise, a survey among educated, older participants found that people visited nature more often during the pandemic [55].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These findings were similar to those found in a majority white, high-income sample from Vermont during the pandemic, showing that participation in nature-related physical activity increased and was associated with income, sex, and employment [45]. Likewise, a survey among educated, older participants found that people visited nature more often during the pandemic [55].…”
Section: Discussionsupporting
confidence: 84%
“…alternative indoor or near-home contacts with nature that were substituted for therapeutic outdoor physical activity in public places. While other emerging research has shown an increase in outdoor activities during the pandemic [45], it was anticipated that outdoor physical activity and usage of parks had declined among cancer patients due to high levels of fear about transmission of the virus in this population [46]. Moreover, it was hypothesized that, in contrast, at-home activities increased.…”
Section: Introductionmentioning
confidence: 99%
“…In another study of a large peri-urban forest near Bonn in Germany expert interviews with forest managers highlighted both an increase in visitor numbers, visits being made at different times of day than previously, and new types of visitors accessing the forest [ 5 ]. A further study in Vermont (USA) found increased participation in walking, wildlife watching and relaxing outside alone [ 6 ]. In England a large scale “People and Nature Survey” in April 2020 found that nearly 50% of adults had spent time outside in green and natural spaces in the previous 2 weeks, with urban green spaces being the most visited type of nature, and the majority of adults (59%) with a garden stating that having a garden was very important to them.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study highlight the need for recovery and the need to experience positive sensations. Morse et al [ 81 ] found in their research that there were significant increases in outdoor activity during the COVID-19 pandemic, especially among women. They discuss whether women may have had a greater need for stress relief during the pandemic and whether they are potentially more likely than men to turn to nature for stress relief.…”
Section: Discussionmentioning
confidence: 99%